El cine social: estrategia de intervención del trabajo social en la formación de actores de desarrollo local. red de microcines la libertad - 2014. - Vereau Reyes, Reymi Katerin (2014)
The new theory of the development guides this study, permitting to understand the need to possess actors of local development in the communities where the Social Work seeks to generate new opportunities for the satisfaction of needs of the persons and / or groups. Specifically we were interested in knowing the contributions of the Social Cinema, as strategy of intervention of the Social Work, in the actors' formation of local development. Being important components of the Social Cinema, the Cinema Forum and the Community Cinema. The importance and contribution of the study, it takes root in demonstrating that the Social Cinema is a strategy to using for the Social Work to the moment to form actors of local development. In spite of the fact that already there exists a method of Social Work, it is necessary that from the practice there are systematized new strategies that they contribute(pay) to this method but especially they help to achieve the aims of human and social promotion of the Social Work. Were considered to be a population of study 24 members of Red de Microcines La Libertad, who allowed to know his processes of formation as actors of local development in the communities where they flow in a direct way. The obtained results facilitated to conclude; that the Social Cinema, as strategy of the Social Work across the Cinema Forum and Community Cinema complements the labour that the Social Workers do to contribute to the Actors' formation of Local Development, and in it adds up to the Human Development of our country. Strategy that allows the Social Work to sensitize across the Cinema Forum, to identify problematic of the communities of a participative way across the Community Cinema, and to achieve feasible commitments of accomplishment to solve conflicts and / or problematic of the community.